Haploinsufficiency of TANK-binding kinase 1 prepones age-associated neuroinflammatory changes without causing motor neuron degeneration in aged mice - Kröger, Clara; Sieverding, Kirsten; Freischmidt, Axel; Satoh, Takashi; Walther, Paul; Mayer, B; Ludolph, Albert C.; Akira, Shizuo; Yilmazer-Hanke, Deniz; Danzer, Karin M; Lobsiger, Christian S; Brenner, David; et al. (Brain communications, 2020)
Loss-of-function mutations in TANK-binding kinase 1 cause genetic amyotrophic lateral sclerosis and frontotemporal dementia. Consistent with incomplete penetrance in humans, haploinsufficiency of TANK-binding kinase 1 did not cause motor symptoms in mice up to 7 months of age in a previous study. Ageing is the strongest risk factor for neurodegenerative diseases. Hypothesizing that age-dependent processes together with haploinsufficiency of TANK-binding kinase 1 could create a double hit situation that may trigger neurodegeneration, we examined mice with hemizygous deletion of Tbk1 (Tbk1+/− mice) and wild-type siblings up to 22 months. Compared to 4-month old mice, aged, 22-month old mice showed glial activation, deposition of motoneuronal p62 aggregates, muscular denervation and profound transcriptomic alterations in a set of 800 immune-related genes upon ageing. However, we did not observe differences regarding these measures between aged Tbk1+/− and wild-type siblings. High age did also not precipitate TAR DNA-binding protein 43 aggregation, neurodegeneration or a neurological phenotype in Tbk1+/− mice. In young Tbk1+/− mice, however, we found the CNS immune gene expression pattern shifted towards the age-dependent immune system dysregulation observed in old mice. Conclusively, ageing is not sufficient to precipitate an amyotrophic lateral sclerosis or frontotemporal dementia phenotype or spinal or cortical neurodegeneration in a model of Tbk1 haploinsufficiency. We hypothesize that the consequences of Tbk1 haploinsufficiency may be highly context-dependent and require a specific synergistic stress stimulus to be uncovered., We found that hemizygous Tbk1 loss does not lead to motor neuron disease or an altered neuroinflammation in mice studied up to an age of 22 months. However, transcriptomic data suggest that Tbk1 haploinsufficiency prepones immune ageing in young mice., - Graphical Abstract